Pengaruh Keluarga dan Lingkungan Ekonomi Terhadap Kinerja Usaha Tahu di Kabupaten Bogor - Febrina Mahliza; Wahyu Budi Priatna; Burhanuddin Burhanuddin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
Micro, small and medium enterprises (MSMEs) has an important role in the national economy. Many MSMEs in Indonesia are family businesses, one of them is “tofu” production in Bogor. Although these businesses are constrained by the prices of raw materials, most of them can survive. The purpose of this study were (1) to analyze the characteristics of the “tofu” business (2) analyze the influence of the family and the economic environment on the performance of the “tofu” business. 114 respondents are collected using purposive sampling method. Data are analyzed using the approach of Structural Equation Modeling (SEM). This study shows that based on the revenue, “tofu” businesses are micro, small and medium enterprises. The results also suggest that the culture and economic environment significantly affect the business performance. Culture can improve business performance, while the economic environment can decrease the business performance.